Contrasting cadmium resistance strategies in two metallicolous populations of Arabidopsis halleri. Issue 1 (2nd January 2018) - Corso, Massimiliano; Schvartzman, M. Sol; Guzzo, Flavia; Souard, Florence; Malkowski, Eugeniusz; Hanikenne, Marc; Verbruggen, Nathalie
Summary: While cadmium (Cd) tolerance is a constitutive trait in the Arabidopsis halleri species, Cd accumulation is highly variable. Recent adaptation to anthropogenic metal stress has occurred independently within the genetic units of A. halleri and the evolution of different mechanisms involved in Cd tolerance and accumulation has been suggested. To gain a better understanding of the mechanisms underlying Cd tolerance and accumulation in A. halleri, ionomic inductively coupled plasma mass spectrometry (ICP‐MS), transcriptomic (RNA sequencing) and metabolomic (high‐performance liquid chromatography–mass spectrometry) profiles were analysed in two A. halleri metallicolous populations from different genetic units (PL22 from Poland and I16 from Italy). The PL22 and I16 populations were both hypertolerant to Cd, but PL22 hyperaccumulated Cd while I16 behaved as an excluder both in situ and when grown hydroponically. The observed hyperaccumulator vs excluder behaviours were paralleled by large differences in the expression profiles of transporter genes. Flavonoid‐related transcripts and metabolites were strikingly more abundant in PL22 than in I16 shoots. The role of novel A. halleri candidate genes possibly involved in Cd hyperaccumulation or exclusion was supported by the study of corresponding A. thaliana knockout mutants. Taken together, our results are suggestive of the evolution of divergent strategies for Cd uptake, transport and detoxification in different genetic units of A. halleri .